Hubungan Dukungan Keluarga dengan Perilaku Pencegahan Stunting Pada Ibu Hamil - Zia_Novita; Frani Mariana; Desilestia Dwi Salmarini (Jurnal Kebidanan Besurek, 2026)
Stunting is a growth disorder in children characterized by impaired physical development due to prolonged inadequate nutritional intake. This condition is typically identified during the toddler period, but its causative factors often emerge as early as the pregnancy phase. The family's role in providing support to pregnant women is a crucial element in stunting prevention efforts. Strong family support can help pregnant women maintain healthy lifestyles and prioritize nutritional needs throughout pregnancy. This study was conducted to investigate the relationship between family support and pregnant women's behaviors in preventing stunting in the service area of Puskesmas Pembantu Jingah. This study employed a correlational analytic design using a cross-sectional approach. A total of 30 participants were selected through saturated sampling. Data were collected by distributing questionnaires to respondents, while data analysis involved processing and chi-square testing to examine relationships between the studied variables. The study findings indicated that the majority of participants (60%) fell into the low family support category, with only 13% in the good category. Similarly, stunting prevention behaviors among pregnant women were predominantly low (57%), with just 16% classified as good. Bivariate analysis confirmed a significant correlation between family support and stunting prevention efforts among pregnant women at Puskesmas Pembantu Jingah (p=0.001). Family support is closely linked to pregnant women's behaviors in preventing stunting. Family involvement and encouragement can motivate pregnant women to adopt healthier habits for early stunting prevention.